How to take arms against central apneas in heart failure. (3rd October 2017) - Borrelli, Chiara; Aimo, Alberto; Mirizzi, Gianluca; Passino, Claudio; Vergaro, Giuseppe; Emdin, Michele; Giannoni, Alberto
ABSTRACT: Introduction Despite being a risk mediator in several observational studies, central apneas are currently orphan of treatment in heart failure. After the neutral effects on survival of two randomized controlled trials (RCTs) based on the use of positive airway pressure (the CANPAP and SERVE-HF trials), two alternative hypotheses have been formulated: 1) Periodic breathing/Cheyne-Stokes respiration (PB/CSR) in HF is protective. Indeed, the Naughton's hypothesis assumes that hyperventilation leads to increased cardiac output, lung volume, oxygen storage and reduced muscle sympathetic nerve activity, while central apnea to respiratory muscle rest and hypoxia-induced erythropoiesis. 2) The use of positive airway pressure is just a wrong treatment for PB/CSR. If this is the case, the search for novel potential alternative treatment approaches is mandatory in HF. Areas covered This review will focus on the crucial issue of whether PB/CSR should be treated or not in HF, first by outlining the ideal design of pathophysiological studies to test the Naughton's hypothesis and second by summarizing the treatment strategies so far proposed for PB/CSR in HF and identifying the most promising options to be tested in future RCTs. Expert commentary It is likely that PB/CSR may be compensatory in some cases, but after a certain threshold (to be defined) it becomes maladaptive with negative prognostic meaning in HF. The development of a pathophysiologically based treatment targeting feedback resetting and neurohormonal activation underlying PB/CSR is likely to be the best option to obtain survival benefits in HF.